Pengaruh pemutihan pajak dan samsat online pada kepatuhan wajib pajak - Yulianto, Anton eko; Rahayu, Yuliastuti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This research aims to find out the effect of tax amnesty and Samsat online on the taxpayers’ obedience in paying the tax vehicle. While, the tax amnesty is one of the government policies in encouraging taxpayers who are late in paying their tax vehicle by giving no sanction toward their out of date payment. Meanwhile, Samsat online is one of the new breakthrough systems in having tax vehicle payment in every Samsat offices within one province. The data is primary data, taken from questionnaires which were distributed to one hundred students of STIESIA including Diploma Three, Strata One, Strata Two and Strata Three education levels. Moreover, the data collection technique used Accidental Sampling, in which the sample was chosen accidentally among respondents by the researcher. From the research results, it concluded the tax amnesty had significant effect on taxpayers’ obedience in paying the tax vehicle, because taxpayers’ who are in arrears feel that they are given relief without being subject to fines so that they are enthusiastic about paying their taxes immediately. On the other hand, Samsat online had insignificant effect on the taxpayers’ obedience in paying the tax vehicle, because there are still the taxpayers’ who do not understand how to pay taxes online.